(untitled) (Indian Journal of Public Health Research & Development, 2021)
[Background] Cognitive dysfunction after a stroke is normal, but it is underdiagnosed and has a bad prognosis. In 40-70 percent of stroke survivors, there is a degree of cognitive dysfunction. Similarly, psychometric issues such as anxiety and depression are normal following stroke but are mostly untreated, resulting in a patient’s poor quality of life. Whereas it also has an effect on a person’s rehabilitation. The use of traditional methodology has certain beneficial effects, but it is not necessarily handled with the individual’s own interests in mind. Virtual reality, on the other hand, seems to play a role in dealing with such issues, especially where they are linked to neurological disorders. Virtual reality navigation has the potential to enhance basic cognitive functions such as visuo-spatial perception, executive performance, and attention, both of which can affect one’s psychological state and aid in functional rehabilitation. Cognitive deficits and social issues must be addressed because they have a detrimental impact on functional abilities and quality of life. [Methodology] Twenty-three participants between the ages of 40 and 60 with a stroke diagnosis were chosen. Participants were split into two groups: Group A, which received Virtual Reality induced environmental and habitual navigation as well as Conventional Physiotherapy, and Group B, which received Conventional Physiotherapy as well as cognitive training and relaxation for 4 weeks of duration. The Montreal Cognitive Assessment (MoCA), Hamilton Anxiety Rating Scale (HARS), Hamilton Depression Rating Scale (HDRS), and Functional Independence Measure (FIM) were used to conduct pre and post intervention evaluations. [Conclusion] The study found that combining virtual reality-induced environmental and habitual navigation with conventional physiotherapy improves cognitive control, psychological function, and functional recovery in stroke patients more effectively than treating them with conventional physiotherapy alone.